Arabic Proficiency Test at Institut Agama Islam Negeri (IAIN) Kediri: (Descriptive Analytical Study) - Munjiyat (UIN Syekh Wasil Kediri, Indonesia, 2024)
اختص البحث بمحاولة الكشف عن اختبار الكفاءة في اللغة العربية بجامعة كديري الإسلامية الحكومية، من ناحية الأداء، وأسئلة الاختبار والتقييم. واستنهج البحث بالمنهج الوصفي التحليلي وذلك من خلال المقابلة والملاحظة في عملية إعداد الاختبار، والتحليل العميق في أسئلة الاختبار وكيفية تقييمه وحساب درجاته. يتم إجراء الاختبار من قبل مركز تطوير اللغة، وهو مخول بتصميم أسئلة الاختبار وإدارتها بشكل واسع، لا يعتمد بمعايير المجلس الأمريكي لتعليم اللغات الأجنبية أو بالإطار المرجعي الأوربي المشترك، لكن عندها مميزات خاصة في الإجراءات، والأسئلة، وكيفية التقييم. يهدف الاختبار إلى قياس مدى كفاءة المتقدمين في مهارة الاستماع والقراءة والقواعد والكتابة. إن مركز تطوير اللغة بذل الجهد الأكاديمي الخاص لتصميم الاختبار، وذلك بعدم المعايير المعتمدة الدولية أو الوطنية في اختبار الكفاءة في اللغة العربية لغير الناطقين بها. This research aimed to explore the Arabic Language Proficiency Test at Kediri State Islamic University in terms of performance, test questions, and assessment. The research adopted a descriptive analytical approach through interviews and observations during the test preparation process, as well as in-depth analysis of the test questions, evaluation methods, and scoring. The test is administered by the Language Development Center. It is authorized to design and administer the test questions on a broad scale. It does not adhere to the standards of the American Council on the Teaching of Foreign Languages or the Common European Framework of Reference, but it has its own unique features in its procedures, questions, and assessment methods. The test aims to measure applicants' proficiency in listening, reading, grammar, and writing skills. The Language Development Center has made a dedicated academic effort to design the test, without meeting international or national standards for the Arabic Proficiency Test for Non-Native Speakers.